Anti-bacterial effect of essential oil extracted from homegrown Origanum vulgare L and Azadirachta indica tree on pathogenic bacteria - Prapti, Jarin Tusnim; Sumaiya, Kazi; Maliha, Farhat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.